Compression behavior of large-scaled cylindrical GFRP chimney liner segments. (15th January 2020) - Cheng, Shi; Feng, Peng; Meng, Xinmiao; Li, Zhiyuan; Du, Jike
Abstract: As a pivotal anti-corrosion structure in the wet flue gas desulfurization system, the huge filament-wound GFRP (glass fiber-reinforced polymer) tube is often employed as the chimney liner. However, the study on its mechanical properties is rare. Three large-scale stiffened cylindrical GFRP chimney liner segments were tested under the axial compression, including an integrated filament-wound chimney liner specimen with two ring stiffeners, a specimen with two ring stiffeners cut into two segments and joined by a hand-wound technique, and a specimen with an outside ring bracket. The failure modes, load-displacement relationships, variation of strains during the loading process, were acquired by test. The effects of ring stiffeners on the mechanical behavior, service reliability of the joint between the two segments of the chimney liner, and the reliability of the ring bracket were examined. Comparisons between theoretically calculated stiffness and experimentally measured stiffness were discussed. Finally, finite element analysis was performed to examine the failure modes and axial load-displacement behavior of the investigated chimney liners. Different ranges of diameter to thickness ratios and load eccentricity values were selected to examine their effects on the mechanical behavior of chimney liners. Finally, suggestions on the design of chimney liner structure were given.